Wetlands verticais para tratamento de águas residuárias da suinocultura com retenção da fração sólida para adubação agrícola - Piovesan, Mateus (2024)
With the global demand for pork protein on the rise, there is an increase in the number of producers starting in the activity and expanding their production, especially in the northwest region of Rio Grande do Sul. Along with this production increase, pig slurry stands out as a significant pollutant of soil and water sources. This raises concerns regarding the treatment and final disposal of this effluent. The objective of this study was to evaluate a treatment system using constructed wetlands aimed at the separation and decontamination of liquid and solid fractions from swine wastewater, with a view to agricultural reuse of the biosolid generated. To achieve this, an experiment was set up with six units of vertical flow constructed wetlands (VFCW), each with a surface area of 0.105 m² and planted with Tifton grass (Cynodon spp.). Swine wastewater (SWW), from an anaerobic lagoon system, was applied to the surface of the VFCWs over a period of 357 days in a feeding cycle: rest ratio of 2:5 days. Three different solid load rates (21, 29, and 43 kg TS/m².year) and two base saturation levels (15 cm and 25 cm) were used for each load rate. Performance monitoring was carried out by evaluating hydraulic drainage capacity, as well as physical and chemical analyses of the influent and effluent wastewater from the VFCWs, monitoring the evolution of the accumulated solids layer on the surface, along with qualitative characterization of this layer in terms of macro and micronutrients, and determining the nutrient content in the Tifton grass biomass. The evaluation of VFCWs' hydraulic performance showed periods of low drainage during times of high rainfall, with improvement after significant solids accumulation on the surface. The VFCWs enabled significant removal of TS (66%), TSS (91%), COD (83%), Total N (80%), and NH4 + - N (79%) in the wastewater. The units with the best performance across all analyzed parameters were those with the lowest load rate, 21 kg TS/m².year. In terms of the accumulated solid fraction, the VFCWs demonstrated the ability to generate solid organic fertilizer with high nutrient content for plants. These results highlight the potential of VFCWs in SWW treatment, aligning with sustainability and circular economy principles, adding value to the treatment byproducts.